INTERNATIONAL AGREEMENT AND MEMORANDUM OF UNDERSTANDING – PROBLEMS OF TRANSLATION - OMES, Aneta (Comparative Legilinguistics, 2014)
The article aims at characterizing selected features of the international agreements and Memorandum of Understanding. It presents general characteristic of agreements and terminology used in both types of these kinds of documents. The author has explained the meaning and the main aim of using the Memorandum of Understanding instead of the standard international agreements. This article indicates the similarities between both of these documents resulting in many misunderstandings between parties to such agreements. It also presents the differences between them in order to show the right direction while drafting such documents. The author has also presented the consequences that may appear when the specified terminology is not followed.